The antimicrobial effects of Cold Atmospheric Plasma jet on microorganisms causing dental caries (in vitro study) (Mustansiria Dental Journal, 2023)
Background: The common microorganism in caries process are Streptococcus mutans and Lactobacilli. Candida albicans have correlation with Streptococcus mutans  for enhanced dental caries. Cold Atmospheric Plasma (CAP) is called as non-thermal as result of electrons are more heated than heavy particles which are at room climate. CAP jets are ionized native gas outflow, produced underneath typical pressure through microwaves, high frequency or pulsed direct current employing noble gases. There are many application of CAP in dentistry: in periodontology, implantology, prosthodontic, operative dentistry and in cariology. This study aimed to measure the sensitivity of the S. mutans and C. albicans to CAP jet. Material and methods:  In this experiment, newly developed Cold atmospheric plasma jet (Iraqi made) using argon gas at a Gas flow rate 10 l/min, 175volt and Frequency 2.45 GHz At room temperature such that the nozzle tip had a maximum distance of 2mm from the agar plate. Cold atmospheric plasma effect was tested at different times on the viable numbers of Streptococci mutans and Candida albicans.  Result: Through the irradiation of CAP jet on agar plates the antimicrobial efficacy  for S. mutans and C. albicans was measured at different time the 3, 6, 9  minutes. Multiple pairwise comparisons using Tukey HSD showed there is significant reduction of colony forming unit (CFU) for Streptococci mutans by plasma at all time compared to  control. multiple pairwise comparisons using Tukey HSD  showed there is highly significance differences for C. albicans was observed  for all times  in comparison to control (p